Cassava starch content and its relationship with rainfall - Moreno Cadena, Leidy Patricia; Gourdji, Sharon (2015)
This study evaluates the relationship between the fluctuations of starch content in cassava and the seasonal behavior of rainfall. A statistical model was developed relating precipitation variables with the starch content of cassava deliveries to the processing factory “Almidones de Sucre” in the Caribbean coast of Colombia. This model shows that there is a relationship between the decrease of cassava starch content and high rainfall during the last month before harvest. Similarly, the onset of precipitation after a dry period during the last 3 months before harvest creates lower starch contents.